Introducing sedimentology - Jones, S. J. (Dunedin Academic Press Ltd, 2015)
This book covers all of the rudimentary aspects of sedimentology, including different types of sedimentary rocks, sedimentary structures, and environments of deposition of sediments. The application of sedimentology in the search for hydrocarbons and other valuable economic resources is explained. Written for students, amateur enthusiasts, and professional geologists, the book provides a succinct and accessible introduction to the science of sedimentology. It is generously illustrated with many explanatory line diagrams and color photographs. Technical terms are kept to a minimum throughout the book, but a glossary of terms is provided.